Management in construction sites: a case study in the city of Sousa-PB (Research, Society and Development, 2021)
The construction industry is an area that comprises a large number of variables, being developed in a changing and dynamic environment, which makes managing a work/construction an extremely complex job. In this sense, the aim of this study is to analyze the production processes in a construction site in a municipality in the interior of Paraíba. To achieve the objectives of the work, a case study was carried out, quantitative and qualitative, with a descriptive procedure. The referred work was a work of necessity, since the bus terminal had a high demand for services, having its production capacity restricted due to its precarious structural state for operation. Data were collected through a checklist, based on studies by Amorim (2018) who analyzed the planning and production process at a construction site. The results showed that the researched construction site can be classified with regular results regarding "Provisional Facilities" and poor in "Security", and "Material Handling and Storage". Such detected problems have a negative impact, mainly on production processes, by preventing the organization from improving its productivity and competitiveness indicators. Among the points to be improved, the results showed the issue of garbage, incorrect storage, the lack of use of PPE and issues related to the safety and health of employees.